Docking Paradigm in Drug Design - Sulimov, Vladimir B.; Kutov, Danil C.; Taschilova, Anna S.; Ilin, Ivan S.; Tyrtyshnikov, Eugene E.; Sulimov, Alexey V. (Current Topics in Medicinal Chemistry, 2021)
Docking is in demand for the rational computer aided structure based drug design. A review of docking methods and programs is presented. Different types of docking programs are described. They include docking of non-covalent small ligands, protein-protein docking, supercomputer docking, quantum docking, the new generation of docking programs and the application of docking for covalent inhibitors discovery. Taking into account the threat of COVID-19, we present here a short review of docking applications to the discovery of inhibitors of SARS-CoV and SARS-CoV-2 target proteins, including our own result of the search for inhibitors of SARS-CoV-2 main protease using docking and quantum chemical post-processing. The conclusion is made that docking is extremely important in the fight against COVID-19 during the process of development of antivirus drugs having a direct action on SARS-CoV-2 target proteins.
Keywords: Mpro